Generative AI In The Context Of Intellectual Property Law: Urgency, Challenges, And Legal Protection - Mantiqa, Yuka Latieful; Hayati, Mulida; Nugraha, Satriya (Journal of Law, Politic and Humanities, 2025)
The rapid development of generative Artificial Intelligence (AI) technologies such as OpenAI and Stable Diffusion has created a complex dilemma in copyright protection in Indonesia. Generative AI, which is capable of producing works of art, music, and writing by imitating human artistic styles through the use of training data from various sources without permission, poses a serious threat to the originality of works and the economic well-being of original artists. This study identifies significant legal gaps in Indonesia's legal system, where AI is not recognized as a legal entity under Article 1367 of the Civil Code, the Information and Transactions Law (ITE Law), the Patent Law, the Copyright Law, and Government Regulation No. 71 of 2019, making it difficult to hold AI accountable for copyright infringements it causes. Using a normative legal research method with a legislative and comparative approach, the study identified three main issues: the absence of specific AI regulations, the use of copyrighted data without permission, and productivity disparities that harm original creators. Comprehensive solutions include the creation of specific AI regulations, the implementation of blockchain technology, and the adoption of international best practices to create a sustainable creative ecosystem.